Estudios de las propiedades termoluminiscentes y fotoluminiscentes del ZrO2:TR y su aplicación a la dosimetría de la radiación Ionizante - Rivera Montalvo, Teodoro (Universidad Autónoma Metropolitana, 2002)
The increased use of ionising radiation in the diagnosis and therapy of some diseases as well as the modern radiation diagnosis and radiotherapy equipment available make necessary the use of a highly reliable dosimeter which be able to measure more and more low energy radiation. In other hand, it is known that humanity is constantly exposed to the UV natural radiation reaching the earth surface. An important part of the UV spectrum it is considered as low energy ionising radiation. This make necessary to do an aáequate evaluation of tire dose aosorbed by man due to UV radiation. UV dosimetry using thermoluminescence (TL) has been suggested in the past and offers the advantage of being able to place the dosimeters, without requiring any special monitoring. A similar technique to measure charges released into the detector material after it is exposed to radiation in which the light emitted is proportional to absorbed dose as a result of a subsequent illumination of the sample with light, is named Optically Stimulated Luminescence (OSL). This technique has an advantage over conventional TL method due that the readout method is all optical, requiring no heating of the samples. The use of OSL in radiation dosimetry has not been extensively reported, mainly because of the lack of a good luminescent material, which has both high sensitivity to radiation, and high optical stimulation efficiency. However, the use of OSL as a personal dosimetry method, is not yet so widespread, despite the fact that its use in this field has a much longer genesis. Firstly, it was suggested for dating application. The aim of this work is to study the main dosimetric characteristics of Zr02 and its application in environmental radiation and personal dosimetry, by means of both TL OSL method. In order to prepare a thermoluminescent material to be used in dosimetric applications, it is necessary to perform a thermal treatment process, usually called annealing. Optimal thermal annealing consisted in heating at 300°C during 10 min. Dosimetric properties studied were: glow curve, sensitivity, linearity, repeatability and fading. Each experimental data point represents the average of at least ten measurements. To investigate the glow curve and other thermally and optically stimulated luminescent properties ofZr02, samples were individually exposed to a UV/light beam from a Xe lamp coupled with a monochromator to select different wavelengths between 200 and 400 nm and the same samples were exposed to beta radiation. To determine the linearity, samples were exposed to an UV light beam of 260 nm wavelength and "Srm beta radiation source by varying the exposure time. To investigate repeatability properties a set of samples was exposed repeatedly for at least 10 times. Fading was determined for exposing samples at ionising radiation and storing them in the dark at room temperature for different periods of time The most attractive characteristic of ZrOs is its very high sensitivity to UV radiation. Thermoluminescence (TL) glow curve of Zr02+PTFE showed one peak centered in 180°C, while the samples exhibited two peaks at 200 and 250°C after "Srm beta particles radiation; its TL response as a function of beta particles dose was linear in the range from 2 to 60 Gy. Repeatability along 10 cycles was 1.8%. Fading at room temperature was 3.8 per month. Typical Optically Stimulated Luminescence (OSL) decay of light intensity showed a dependence on illumination time. OSL response of Zr02 samples as a function of irradiation time was linear in the range of 5 to 900 seconds. OSL signal showed more than one components. LM-OSL curve showed a maximum approximately at 41 seconds of illumination time. LM-OSL curve of ZrOn showed an initial peak followed b a long tail one. OSL response as a function of absorbed dose showed linear from 10 to 200 Gy to z Sr/?? beta particles. The TL measurements were made in a Harshaw 4000 TL analyzer connected to a PC to record and process the data. The TL signal was integrated from room temperature up to 300°C using a heating rate of lO"C/s. OSL measurements were made using the Riso automated TUOSL reader DA - 15, using a green LED array with a wavelength of 523 nm and 300 mW/cm2. All both TL and OSL measurements were carried out in a nitrogen atmosphere in order to erase any information undesirable. TL and OSL signal was absent in Zr02+PTFE samples which had not been irradiated, as well as those which had been heated to 300°C after. Re-irradiation after heating caused a reappearance of the stimulated luminescence. This effect confirms that the stimulated luminescence from irradiated samples was a result of the interaction of ionising radiation with matter. Then we can say TL response is a very close function the annealing temperature of the structural changes which, furthermore, produces in Zr02. This conclusion is confirmed by the results showed in the TL response and the post-irradiation annealing to samples irradiated. Thus we may conclude that the temperature dependence upon the luminescent efficiency of the recombination process is strongly connected to the specific emission of individual glow peaks. This affirmation is very important for dosimetric applications, mainly to environmental and personal dosimetry applications where the TL background has importance. In other specific situations, as radiation protectior purpose in diagnostic therapy or in radiotherapy where a high accuracy is necessary, an individual background is used and checked periodically to avoid any possible mistakes in the dose determination owing to large variations of the background.